The Role of Artificial Intelligence in Enhancing Supply Chain Efficiency and Risk Management - Naveed Rafaqat Ahmad; Maryam Jameela Qadri (Global Journal of Multidisciplinary and Applied Sciences, 2025)
The increasing complexity and volatility of global supply chains have intensified the need for intelligent, data-driven solutions to enhance operational efficiency and mitigate risks. Artificial Intelligence (AI) has emerged as a transformative force in supply chain management, enabling predictive analytics, real-time decision-making, and adaptive risk management. This study examines the role of AI technologies—such as machine learning, predictive modeling, natural language processing, and intelligent automation—in improving supply chain efficiency and resilience. Drawing on recent empirical studies and conceptual frameworks, the paper explores AI-enabled demand forecasting, inventory optimization, logistics planning, and risk anticipation. The findings indicate that AI-driven supply chains achieve superior performance in cost reduction, responsiveness, and disruption management compared to traditional systems. The study concludes by highlighting implementation challenges, ethical considerations, and future research directions, particularly in the context of developing economies like Pakistan.